Sinergi Triple Helix untuk Meningkatkan Edukasi Pengelolaan Sampah Masyarakat melalui Bank Sampah di Desa Panjunan - Nailul Ulah Al Chumairoh Machfud; Dwi Astutiek; Agus Setyawanto; Abdul Quddus Salam; Asyhari; Nurul Hadi (AlMurtado Journal of Social Innovation and Community Service, 2024)
Waste management remains a critical issue in many rural areas, including Panjunan Village. The lack of public awareness regarding sustainable waste handling highlights the need for educational interventions involving multiple stakeholders. This community service project aims to enhance public education on waste management through the development of a waste bank using the Triple Helix approach, involving collaboration among universities, local government, and the community. The methods included awareness campaigns, training sessions, and technical assistance in establishing and managing the waste bank. The results indicated a significant improvement in community knowledge and active participation in household waste sorting and management. Furthermore, the formation of a waste bank management team and the engagement of local partners served as indicators of the success of this collaborative approach. Thus, the Triple Helix synergy proves effective in promoting environmental awareness and empowering sustainable waste management at the village level.